Unipolar resistive switching behavior of amorphous SrMoO4 thin films deposited at room temperature. Issue 3 (15th February 2017) - Hu, L.; Lin, G.T.; Wei, R.H.; Luo, X.; Tang, X.W.; Zhu, X.B.; Song, W.H.; Dai, J.M.; Sun, Y.P.
Abstract: Amorphous SrMoO4 (SMO) thin films were deposited on Pt/Ti/SiO2 /Si substrates at room temperature by pulsed laser deposition and the resistive switching (RS) behavior of the Au/SMO/Pt devices was investigated. The Au/SMO/Pt devices exhibit typical unipolar RS behavior with excellent switching parameters as follows: high resistance ratio ( 10 5 ) between the low resistance state (LRS) and high resistance state (HRS), non-overlapping switching voltages, and good endurance and retention characteristics. Detailed analysis of their current-voltage characteristics reveals that the conduction mechanisms are Ohmic conduction in the LRS and lower voltage region of HRS, and Poole-Frenkel emission in the higher voltage region of the HRS. Temperature dependent resistance measurements, combined with x-ray photoelectron spectroscopy and model analysis indicate that the unipolar RS behavior of the Au/SMO/Pt devices could be understood by a conical conducting filaments (CFs) model in which the conical CFs are composed of oxygen vacancies. The conical CFs extend from the cathode to anode during the forming process and the observed RS behavior occurs in the localized region near the anode. These results suggest that the room-temperature- deposited amorphous SMO thin films could find potential application in nonvolatile RS memory.